Perkembangan Pendidikan di Eropa Pada Masa Abad Pencerahan - Kusmawati, Heny; Munawaroh, Ainatul; Hana, Muhammad Yusrul (Educationist: Journal of Educational and Cultural Studies, 2023)
Education comes from the Latin "Ducare" which means to guide, direct, and lead, the prefix "e" which means out. Education is a process of transforming knowledge both in natural science and intellectual knowledge from the earlier generation to the next. This process lasted from prehistoric times to modern times. Not only happening in Indonesia, this process also takes place throughout the world. Western philosophy in the Middle Ages (479-1492M) can also be said to be the "Dark Ages", this opinion is based on an approach to church history. If there is a thought that is contrary to the teachings of the church will get a severe punishment. By collecting data through literature study and then conducting content analysis, this research found that this can be achieved by a critical process of normal science. Reflecting on the success of the West over several centuries, the strategy adopted is to place the sacredness of knowledge not on content but on function and purpose, present it in the form of scientific truth in front of the public, and change the orientation of education which then gives birth to inventors (discoveries) and creators (inventors).